Search, Rigidities and Unemployment Dynamics - Fakhraldin Zaveh (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper, I study the sources of cross-country differences in unemployment dynamics. Elsby, Hobijn and Sahin (forthcoming) find that in Anglo-Saxon economies unemployment fluctuations are mainly driven by changes in the outflows out of unemployment, while in continental European and Nordic countries changes in inflows into unemployment are almost equally important. I provide evidence that a category of labor market regulations which I refer to as the restrictive regulations raise contributions of inflows into unemployment. On the contrary, higher firing costs reduce the importance of this driver of unemployment dynamics which is in line with the literate. I introduce an aggregate regulatory rigidity into an otherwise standard search and matching framework. The consequent model is consistent with the mentioned fact.
Keywords: E24; 330; Unemployment Dynamics; Search and Matching; Rigidity; Restrictive Regulations